CORPORAL PUNISHMENT DAN PENJATUHAN HUKUMAN - Emmilia Rusdiana, (Pelangi Ilmu, 2009)
Abstract Corporal punishment is a specific violence performed by teacher to children on behalf of disciplining or educating children, with the intention want to be reached if it applied on children, and this corporal punishment existence is based on the national educational system acts. While, for the pronouncement of sentence base as the general form of the corporal punishment it can be reviewed in various aspects, that is, corporal punishment in the criminal law perspective, human rights, and Children Protection Acts.